Accessing the field: methodological difficulties of research in schools - Catriona Oates; Nasim Nighet Riaz (University of Aberdeen, School of Education, 2016)
This paper aims firstly to situate educational research in the current policy context and discuss the accounts of two early career researchers where accessing the research field has been problematic. Secondly it aims to explore the 'relational ties' of early career researchers as they attempt to gain access to the research field and co-operation of research participants, using their experiences and literature to explain difficulties encountered in their fieldwork. Gaining access to the research field is an essential step for researchers but can be overlooked in literature and underestimated by researchers. Concern with fieldwork is typically more focused on the subsequent stages of data generation and analysis rather than with the preliminary but fundamental stage of entry which is sometimes underplayed in the research process. Some literature supports this contention (Schatzman and Straus, 1973, Johnson, 1975, Shaffir, Stebbins and Turowetz, 1980). Friedman and Orru (1991) discuss how fieldworkers have long acknowledged the problems of access but often failed to analyse them in a systematic manner. Although access and cooperation are sometimes conflated in literature (Wanat, 2008) they must be clearly understood as two distinct processes (Hammersley and Atkinson, 1995, Glesne, 1999, Bogdan and Biklen, 2003, Rossman and Rallis, 2003). Indeed, gatekeeper approval for access does not de facto guarantee cooperation (Shaffir and Stebbins 1991) which can lead to tension in researcher-participant relationships. Main findings suggest that although helpful in advancing understanding of the access issue, there is still work to be done to minimise mistrust of external researchers and for them to build social and cultural capital to better negotiate spaces in the research field.